An epigraphic monument dedicated to Liber Pater recently found at Ampelum - CIUTĂ, Marius-Mihai; CIUTĂ, Elena Beatrice (Studia Universitatis Babeș-Bolyai Historia, 2016)
This paper describes and transcribes a Roman inscription-bearing altar. The photo of the altar was founded in the PC of a culprit searched for illegal prospections in archaeological sites. The culprit declared that the piece was excavated in the area of the former Copper Processing Factory from Zlatna (Alba County), well known as the former area of municipium Ampelum, the residence of the gold and silver mining administration of Dacia. The fragmentary monument, dedicated to the Liber Pater by a certain Iulius, is missing now (wanted by the Romanian Police). The characteristics of the text and the aspect of the decorated surfaces suggest that it was made by an urban craftsman with experience. The altar may have originated from the municipium Ampelum. Although the great number of Roman vestiges, especially with inscriptions or figurative reproductions (statues, altars, funerary monuments etc.) placed Ampelum, both the settlement and necropolis, among the most dynamic urban centers of the province. The paper is also focused on the problematic of the inefficient protection of the cultural heritage. Rezumat. Un monument epigrafic dedicat lui Liber Pater descoperit recent la Ampelum. Acest studiu descrie și întregește un altar cu inscripţie roman. Fotografia altarului a fost găsită în calculatorul unei persoane cercetate pentru prospecţii ilegale în situri arheologice. Persoana a declarat că piesa a fost descoperită în zona fostului Combinat de prelucrare a cuprului din Zlatna (judeţul Alba), pe teritoriul fostului municipium Ampelum, reședinţa administraţiei minelor de aur și argint din Dacia. Monumentul fragmentar, dedicat lui Liber Pater de un anume Iulius, este acum dispărut, fiind căutat de poliţia română. Caracteristicile textului și aspectul părţii decorate sugerează că a fost făcut de un meșter urban cu experienţă și precizie. Altarul ar putea proveni din municipium Ampelum. Un mare număr de vestigii, inscripţii și monumente figurate (statui, altare, monumente funerare etc.), plasează Ampelum - așezarea și necropola - printre cele mai dinamice centre urbane din provincie. Lucrarea se concentrează și asupra problemei ineficienţei protecţiei patrimoniului cultural. Cuvinte cheie: Liber Pater, altar votiv, Dacia, dosar penal